2021
DOI: 10.1038/s41598-021-84298-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tDCS on working memory training is enhanced by strategy instructions in individuals with low working memory capacity

Abstract: Interventions to improve working memory, e.g. by combining task rehearsal and non-invasive brain stimulation, are gaining popularity. Many factors, however, affect the outcome of these interventions. We hypothesize that working memory capacity at baseline predicts how an individual performs on a working memory task, by setting limits on the benefit derived from tDCS when combined with strategy instructions; specifically, we hypothesize that individuals with low capacity will benefit the most. Eighty-four parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
(67 reference statements)
1
17
1
2
Order By: Relevance
“…The improved selective attention induced by VNS ( Sun et al, 2017 ) might have a larger effect on the spatial attention network and contributed to the difference in the improvement of taVNS on spatial and digit WM performance. Besides, the researches in tDCS found that the modulation of electric field on WM depends on the baseline performance (e.g., Assecondi et al, 2021 ). The individuals or tasks with lower baseline outcome were more likely to have a higher improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The improved selective attention induced by VNS ( Sun et al, 2017 ) might have a larger effect on the spatial attention network and contributed to the difference in the improvement of taVNS on spatial and digit WM performance. Besides, the researches in tDCS found that the modulation of electric field on WM depends on the baseline performance (e.g., Assecondi et al, 2021 ). The individuals or tasks with lower baseline outcome were more likely to have a higher improvement.…”
Section: Discussionmentioning
confidence: 99%
“…According to the magnification-compensation theory, individuals who are already using their resources optimally have less room for improvement, therefore will improve less, expecting a negative correlation between initial performance and gains from cognitive training ( Lövdén et al, 2012 ). Finally, considering our previous findings ( Assecondi, 2021 ), a failure to find an effect of stimulation could also be ascribed to the impossibility, given the small sample size, to focus on individuals with low working memory capacity.…”
Section: Discussionmentioning
confidence: 89%
“…Before starting the first n-back (at baseline, T0) participants were provided with instructions on how to perform the task, depicted in Figure 5 . Instructions follow a general “memorize,” “compare,” and “update” strategy ( Laine et al, 2018 ; Assecondi, 2021 ), applicable to n-back tasks, as we found that efficient strategy use can modulate tDCS effectiveness and can reduce noise due to interindividual differences ( Lövdén et al, 2012 ).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations